Hydraulic Model Investigation on Stepped Spillway’s Plain and Slotted Roller Bucket - Kote, A. S.; Nangare, P. B. (Engineering, Technology & Applied Science Research, 2019)
In ogee spillway, the released flood water from crest to toe possesses a high amount of kinetic energy causing scour and erosion on the spillway structure. The dam projects normally have a stilling basin as an energy dissipater which has specific energy dissipation limitations. The stepped spillway is a better option to minimize kinetic energy along the chute and safely discharge water in the river domain. The Khadakwasla dam is situated in Pune, Maharashtra (India), and has scouring and erosion issues on the chute of ogee spillway and on the stilling basin. The present study develops a physical hydraulic model for the dam spillway with steps, plain and slotted roller bucket as per IS Code 6934 (1998) and IS Code 7365 (2010). Experiments were performed at heads of 4m (low head) and 6m (high head) on the developed physical models, namely on the plain and slotted roller bucket model for the ogee spillway and the plain and slotted roller bucket model for the stepped spillway. It was found that the plain roller bucket of ogee spillway dissipates 81.26% of energy at the low head, whereas the stepped spillway with slotted roller bucket dissipates the 83.86% of the energy at the high head.